An experimental study on the association of ambidextrous latex gloves to hand fatigue - Totaan, Winnie Ann E.
The objective of this study was to determine if there was an association in the use of ambidextrous latex gloves on hand fatigue. The study measured and compared the mean strengths of both the dominant and non-dominant hands of the ambidextrous glove users and the anatomically-fit glove users to see if there was a statistically significant difference between the two types of gloves. The subjects, who were divided into a control (anatomically-fit gloves) and experimental (ambidextrous gloves) were required to perform scaling on a pig's mandible for a maximum of fifty-five minutes and polishing for five minutes the most. Before they began working on the said mandible, the pinch strengths of their hands (with gloves on) were measured specifically the lateral and palmar types of pinch. Three trials were gathered for each type of pinch and the mean average was computed. The procedure was repeated after the subjects were done performing their tasks. The mean central tendency was used to determine the mean strengths of the hand through the 3-way ANOVA and Fischer's Test with a p-value of 0.05 was used to detemine if there was a statistically significant difference between the two types of gloves. The results of the study implied that there was no significant difference between the two types of gloves. In conclusion, the results of the study proved that the association of ambidextrous latex gloves to hand fatigue is statistically insignificant.